2022
DOI: 10.1155/2022/8043841
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves Intestinal Motility through Exosomal miR-34c-5p Targeting SCF/c-Kit Signaling Pathway in Slow Transit Constipation Model Rats

Abstract: Background. The pathogenesis of slow transit constipation (STC) is associated with exosomal miR-34c-5p. Electroacupuncture (EA) improves gastrointestinal motility in gastrointestinal disorders, especially STC. Our study aimed to explore the mechanism by which EA improves intestinal motility by modulating the release of exosomes and the transmission of exosomal miR-34c-5p. Methods. Fifty rats were randomly divided into five groups. STC model rats were induced, and GW4869, the exosome release inhibitor, was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…5-hydroxytryptamine, also known as serotonin, is an indole derivative, which can also enhance the contraction of blood vessels and smooth muscles. Kuang et al 15 have demonstrated that the enhancement of 5-HT immunoreactivity is one of the main factors leading to gastrointestinal motility disorder. In this study, the concentrations of 5-HT and NOS1 in intestinal tissues of rats were measured.…”
Section: Discussionmentioning
confidence: 99%
“…5-hydroxytryptamine, also known as serotonin, is an indole derivative, which can also enhance the contraction of blood vessels and smooth muscles. Kuang et al 15 have demonstrated that the enhancement of 5-HT immunoreactivity is one of the main factors leading to gastrointestinal motility disorder. In this study, the concentrations of 5-HT and NOS1 in intestinal tissues of rats were measured.…”
Section: Discussionmentioning
confidence: 99%